The impact of transparency on hemispheric lateralization of idiom comprehension: An rTMS study. (10th December 2021) - Kurada, Hazel Zeynep; Arıca-Akkök, Elif; Özaydın-Aksun, Zerin; Şener, H. Özden; Lavidor, Michal
Abstract: Previous neuropsychological data have equivocal suggestions concerning hemispheric involvement during idiom comprehension. The possible contribution of idioms transparency to the lateralization of figurative language comprehension has not been investigated using an interference technique. To analyse the cortical lateralization of idiom transparency processing, we employed inhibitory repetitive transcranial magnetic stimulation (rTMS) to the left and right dorsolateral prefrontal cortex (DLPFC) during the processing of opaque idioms, transparent idioms, and non-idiomatic literal phrases. Based on the Coarse Semantic Coding theory, we predicted a greater right hemisphere involvement when processing opaque than transparent idioms. Eighteen young healthy participants underwent rTMS pulses at 1 Hz frequency, 110% of motor threshold intensity for 15 min (900 pulses) in two sessions at one-week intervals. In a semantic decision task, participants judged the relatedness of an idiom and a target word. The target word was figuratively or literally related to the idiom, or unrelated. The study also included non-idiomatic sentences. We found that left DLPFC functions are more critical for comprehension of opaque rather than transparent idioms when referring to the figurative associations of the idioms. Opaque idioms, in the context of their figurative meaning, rely more heavily on left hemisphere resources. This finding suggests that opaque idioms are seemingly processed as one unit. Taken together, we believe that the transparency of idiomatic expressions may play an important role in modulating hemispheric functions involved in figurative language processing. Highlights: The possible contribution of transparency on hemispheric specialization of figurative language comprehension has not been investigated with an interference technique. Left dorsolateral prefrontal cortex functions are more critical at comprehension of opaque rather than transparent idioms, when referring to the figurative associations of the idioms. Transparency of idiomatic expressions might play an important role in modulating hemispheric functions involved in figurative language processing.